2012
DOI: 10.1097/shk.0b013e3182635aca
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation of Traumatic Hemorrhagic Shock Patients With Hypertonic Saline—Without Dextran—Inhibits Neutrophil and Endothelial Cell Activation

Abstract: Background Post-traumatic inflammation and excessive neutrophil activation cause multiple organ dysfunction syndrome (MODS), a major cause of death among hemorrhagic shock patients. Traditional resuscitation strategies may exacerbate inflammation and thus novel fluid treatments are needed to reduce these post-traumatic complications. Hypertonic resuscitation fluids inhibit inflammation and reduce MODS in animal models. Here we studied the anti-inflammatory efficacy of hypertonic fluids in a controlled clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 36 publications
2
59
0
2
Order By: Relevance
“…Across a range of time-points following traumatic injury, ex vivo studies have reported significant alterations in a multitude of neutrophil functions [5][6][7][8][9][10], which are likely to contribute to the development of secondary complications. For instance, sequestration of hyperactive neutrophils in remote bystander organs is thought to underlie the development of both ARDS and MOF, whilst reduced neutrophil function may be one explanation for the increased susceptibility of hospitalised trauma patients to nosocomial infections [2,11].…”
Section: Introductionmentioning
confidence: 99%
“…Across a range of time-points following traumatic injury, ex vivo studies have reported significant alterations in a multitude of neutrophil functions [5][6][7][8][9][10], which are likely to contribute to the development of secondary complications. For instance, sequestration of hyperactive neutrophils in remote bystander organs is thought to underlie the development of both ARDS and MOF, whilst reduced neutrophil function may be one explanation for the increased susceptibility of hospitalised trauma patients to nosocomial infections [2,11].…”
Section: Introductionmentioning
confidence: 99%
“…Animal experiments have shown that hypertonic salt solutions influence the hemodynamics through selective dilation of small arteries that lead to capillaries, supplying oxygen to important organs. Moreover, hypertonic salt solutions are also superior to crystalloid or colloid solutions, in terms of immunomodulatory effect (Chiara et al, 2003;Junger et al, 2012;Kim et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…El SSH arrastra agua desde el intersticio al intravascular, por lo que su aporte se asocia a un aumento en la volemia de 9 a 10 veces el volumen infundido. Estudios experimentales 28 y estudios fisiológicos 29,30 han reportado resultados positivos, especialmente la disminución de marcadores pro inflamatorios. Sin embargo, 2 estudios clínicos aleatorizados no demostraron mejoría en morbilidad o mortalidad con el uso de SSH 7,5% (250 ml en 15 min) versus cristaloides en el pre hospitalario 31,32 .…”
Section: Aporte De Fluidos En Traumaunclassified